Platelet Membranes Coated Gold Nanocages for Tumor Targeted Drug Delivery and Amplificated Low-Dose Radiotherapy - Mingzhu Chen (Frontiers Media S.A., 2021)
Continuous high doses of radiation can cause irreversible side effects and radiation resistance; thus, advanced radiosensitizers are urgently needed. To overcome this problem, we developed a nano platelet radiosensitization system (PCA) by coating the chemotherapeutic drug cisplatin (CDDP) loaded gold nanocages (AuNs) within the platelet membrane. The developed PCA system may enable AuNs to have immune escape and targeting capabilities. After administration, PCA will actively target tumor cells and avoid being cleared by the immune system. Subsequently, CDDP, which destroys tumor cell DNA, can not only kill tumor cells directly but also combine with AuNs, which deposit radiation energy into tumor tissues, reducing RT resistance. In vivo and in vitro studies revealed that the combination of PCA with RT (2Gy) efficiently inhibits tumor proliferation without causing side effects such as inflammation. To conclude, this is the first attempt to use platelet membranes to correctly transport AuNs while also accomplishing low-dose RT, which could help AuNs-based tumor RT become more effective.